Pembelajaran PAI dan Budi Pekerti Berorientasi Projek Penguatan Profil Pelajar Pancasila (P5) di SMP 17 Mukomuko Propinsi Bengkulu - Rusli Rusli; Suhirman Suhirman; Desy Eka Citra Dewi (UIN Fatmawati Sukarno Bengkulu, 2021)
The purpose of this study is (1) To determine the planning of PAI and Character learning oriented to the Pancasila student profile strengthening project (P5) in SMP 17 Mukomuko (2) To determine the implementation of PAI and character learning oriented to the Pancasila student profile strengthening project (P5) in SMP 17 Mukomuko. (3) To find out the evaluation of PAI learning and character education oriented to the Pancasila student profile strengthening project (P5) at SMP 17 Mukomuko. The type of research used in this study is qualitative, data collection techniques are observation, interviews and documentation, data analysis techniques are data collection is data reduction, data presentation, and conclusions and verification. Research results: (1) Planning of PAI learning and character education oriented to the Pancasila student profile strengthening project (P5) at SMP 17 Mukomuko There are 3 stages carried out by SMP N 17 Mukomuko to plan the strengthening of the Pancasila Student Profile, the first is forming a facilitator team. Second, identifying school readiness. Third, determining the dimensions, themes, and time allocation. Fourth is making learning modules and project modules. (2) Implementation of strengthening the Pancasila Student Profile is carried out through 2 activities, namely intracurricular activities and extracurricular activities. Intracurricular activities help strengthen the Pancasila Student Profile through PAI learning. There are 3 extracurricular activities used to strengthen the Pancasila Student Profile, namely, scouts as a mandatory extracurricular activity, speech, hadroh, karate, as an optional extracurricular activity. (3) Evaluation of Strengthening the Pancasila Student Profile at SMP N 17 Mukomuko The assessment of the Pancasila Student Profile is still based only on report cards, intracurricular activities, extracurricular activities, and school culture. We have not conducted an evaluation because the Pancasila student profile strengthening project as a whole because the project theme is ongoing and the themes that can be evaluated per year are 3 project themes.